Pemanfaatan Media Pembelajaran Interaktif Untuk Meningkatkan Pemahaman Konsep Keislaman Dalam Pendidikan Agama Islam - Wildan, Gusti Sab'an; Bunyamin (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
Understanding the concept of Islam in Islamic Religious Education is often hindered by a learning approach that is less engaging and non-interactive. This results in students being less motivated and having difficulty in comprehensively understanding the material. This research aims to explore the utilization of interactive learning media as an effort to enhance the understanding of Islamic concepts among students. This study employs a qualitative approach with a literature review method, analyzing various literature sources related to the use of interactive media in religious education. The research results indicate that interactive learning media can provide a more engaging learning experience, facilitate the understanding of religious concepts, and increase student involvement in the learning process. Therefore, the use of interactive media in Islamic Education is highly recommended to address issues in teaching Islamic concepts in schools. This research is expected to contribute to the development of more effective learning methods that meet the needs of the millennial generation in understanding Islam.